A new hybrid concentrated-winding concept with improved power factor for permanent magnet vernier machine - Xie, Shuangchun (2023)
This paper investigates a high power-factor permanent magnet vernier machine (PMVM) equipped with low-coupling hybrid concentrated-winding (CW). The proposed hybrid-CW, carrying both star- and delta-winding sets, exhibits a good filtering property to both sub- and super-order harmonics. Through the meticulous design of the short coil pitch, the ratio of inductance to magnet flux linkage is decreased, leading to a great improvement in power factor. The proposed low-coupling winding design contributes to further power factor improvement by reducing the inductance while retaining the magnet flux linkage. It is revealed that the mutual coupling between different coils of single phase and that between different windings of three phases are suppressed significantly in the hybrid-CW, thus leading to high power factor and potentially high fault tolerance. Finite element results show that the proposed hybrid-CW PMVM exhibits a significantly improved power factor up to 0.96 from 0.83 and 0.75, as compared with two counterpart PMVMs with open-slot and split-tooth structures, respectively. Benefiting from the magnetic gearing effect, the proposed PMVM has a promising active torque density of 40 Nm/L. Taking end-winding volume into consideration, the proposed PMVM exhibits an actual torque density of 21.98 Nm/L, which is 22.52% and 52.43% higher than the investigated open-slot and split-tooth counterpart PMVMs. Finally, a prototype is fabricated and tested to validate the high-power-factor and high-torque-density features of the proposed hybrid-CW PMVM.